Ten Frequently Asked Questions About Veterans' Transitions Results of a Decade of RAND Work on Veteran Life - Guo, Christopher (RAND Corporation, 2016)
This document compiles the RAND Corporation's body of work on veterans' transitions to civilian life and highlights the breadth of topics RAND has studied. It distills more than a decade's worth of research on many facets of veteran life into a set of ten questions and answers gleaned from this work.